BLI‐MS: Combining biolayer interferometry and mass spectrometry. Issue 9 (5th January 2022) - Jung, Vincent; Roger, Kévin; Chhuon, Cerina; Pannetier, Louise; Lipecka, Joanna; Gomez, Josué Sulub; Chappert, Pascal; Charbit, Alain; Guerrera, Ida Chiara
Abstract: Biolayer interferometry (BLI) is a technology which allows to study the affinity between two interacting macro‐molecules and to visualize their kinetic of interaction in real time. In this work, we combine BLI interaction measurement with mass spectrometry in order to identify the proteins interacting with the bait. We provide for the first time the proof of concept of the feasibility of BLI‐MS in complex biological mixtures.